Assessing Critical Thinking in Solubility and Solubility Product Constants: Development of an E-Portfolio-Based Assessment Instrument - Triannisa Rahmawati; Wiwi Siswaningsih; Miarti Khikmatun Nais; Nahadi Nahadi; Won Koo Lee; Arina Ulfa Mawaddah (Universitas Syiah Kuala, 2026)
Measuring students' critical thinking skills (CTS) on the topic of solubility and solubility product constant (Ksp) is currently still hampered by the limited assessment instruments that are capable of evaluating the reasoning process authentically and comprehensively. This research aimed to develop an e-portfolio assessment tool on solubility and Ksp subject matter that can help enhance CTS of students. Two assessment instruments have been developed, namely tasks and rubrics. This research used research & development methods and followed the 4-D model, but consisting of define, design, and develop phases only, with limited trials. Research instruments used as data collection tools are interview guidelines, validation sheets, observation sheets, tasks, and rubrics. Respondent of this research was 20 students coming from class XI of one of the high schools located in Bandung city. Functions designed as an e-portfolio assessment tool on solubility and Ksp subject matter have successfully been developed through mind mapping, essay analysis questions, and experimental reports of students. Results have ascertained that research instrument is valid, based on CVR value range, namely, 0.60-1.00, and could be considered reliable as indicated by Cronbach's alpha reliability of value range, namely 0.62-0.93. Based on limited trials, students demonstrated moderate improvement in CTS in most tasks. Only three questions showed significant improvement. Of the nine CTS indicators, most were in the moderate category. Only one indicator, observing research results, was in the high category. However, these results indicate a positive impact of using the instrument on improving CTS. Based on the results, this research has ascertained that e-portfolio assessment tool on solubility and Ksp can help enhance CTS of students on moderate category